2021
DOI: 10.1136/jitc-2021-003093
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kα inhibitor CYH33 triggers antitumor immunity in murine breast cancer by activating CD8+T cells and promoting fatty acid metabolism

Abstract: BackgroundThe phosphatidylinositol 3-kinase (PI3K) is frequently hyperactivated in cancer and plays important roles in both malignant and immune cells. The effect of PI3Kα inhibitors on the tumor microenvironment (TME) remains largely unknown. Here, we investigated the modulation of the TME by a clinical PI3Kα-specific inhibitor CYH33.MethodsThe activity of CYH33 against a panel of murine tumors in the immune-competent context or athymic mice was detected. Single-cell RNA sequencing and multi-parameter flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…A statistically significant difference was found between FASN and CD8 + T-cells in HNSC, KIRC, OV, and BRCA ( Figure 16 ). These results were consistent with those of published studies, which revealed that phosphatidylinositol 3-kinase α inhibitor could promote fatty acid metabolism to activate CD8+T cells, and a combination of the inhibitor and FASN inhibitor could enhance immunity to decrease breast tumor growth [ 44 ]. A favorable relationship was also found between FASN expression and cancer-associated fibroblasts in CESC, KIRC, KIRP, OV, and UVM.…”
Section: Discussionsupporting
confidence: 92%
“…A statistically significant difference was found between FASN and CD8 + T-cells in HNSC, KIRC, OV, and BRCA ( Figure 16 ). These results were consistent with those of published studies, which revealed that phosphatidylinositol 3-kinase α inhibitor could promote fatty acid metabolism to activate CD8+T cells, and a combination of the inhibitor and FASN inhibitor could enhance immunity to decrease breast tumor growth [ 44 ]. A favorable relationship was also found between FASN expression and cancer-associated fibroblasts in CESC, KIRC, KIRP, OV, and UVM.…”
Section: Discussionsupporting
confidence: 92%
“…Hypoxia is an internal environment in almost all solid tumors. Hypoxia interacts with fatty acid metabolism and can regulate tumor immunity ( 17 , 18 ). Therefore, the differences in the immune cell content and hypoxia signal pathway between the cluster1 and cluster2 groups were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Reports using select PI3K inhibitors suggest potential use toward achieving similar results. Sun et al report on the compound CYH33 (an inhibitor of the PI3K alpha isoform) (43). CYH33 exhibited a potent antitumor activity in an immune-competent context by enhancing the infiltration and activation of CD8+T and CD4+T cells, while attenuating M2like macrophages and regulatory CD4+T cells.…”
Section: Optionmentioning
confidence: 99%